THE EFFECTIVENESS OF A TECHNICAL COMMUNICATION COURSE IN A MALAYSIAN TECHNICAL UNIVERSITY: ENGINEERS’ PERSPECTIVES - Indra Devi, S.; Husin, Noraini; Subatira, B. (Journal of Human Capital Development (JHCD), 2010)
Communication has become a crucial requirement for all engineers. The global engineering world has created demands on engineers to be able to collaborate on cross-functional teams, manage virtual-project teams and write for multiple complex audiences. This study investigates on the engineering undergraduates’ perceptions about the effectiveness of the Technical Communication course in terms of course content as well as viable suggestions to improve on the course. The instruments that were used for data collection in the study are survey questionnaires and recorded interviews. The findings of the evaluation by the undergraduates reveal that on the overall the effectiveness of the course content is at a moderate level. Thus, this is indicative of the fact that the Technical Communication course needs to be revised in terms of the course content. The respondents have also provided viable solutions to improve on the course. Keywords: technical communication, assessment, course content, teaching material, engineers’ perspectives